An English Teacher’s Reflective Practice in English Foreign Language (EFL) Classroom - Rihali Indra Munggaran (Jurnal sosial dan sains, 2022)
The duty of the teacher is not merely transfering knowledge but he/she should be aware to any students’s difficulties by carry on reflective practice during or after learning process. Therefore, This study examine how does the teacher reflect the teaching process in EFL classroom. In this respect, qualitative approach and descriptive qualitative method are used in this study. The study explored 6 participants such as one English teacher as primary source and five students as secondary source. The data were collected via observation, interview and documentation. The documentation is presented in the form of teacher’s diary which is teacher can express about his/her feelings, experiences, difficulties and problems in a diary writing. The findings of the study revealed that the teacher using diary writing as a strategy to reflect the teaching process after learning activity has finished. The teacher always helps students, who are difficult to understand the material repeatedly. Reviewing the material is frequently use to check whether students still remember or forget and giving some questions related to the material to make students focus on learning process. The teacher arranged the technology to be used in learning activity to make students more interest on English subject.